Modeling user's trust in M-commerce acceptance: a conceptual framework in context of Pakistan - Rind, M. Malook; Koondhar, M. Yaqoob; Hyder, Mansoor; Shah, Asadullah (Institute of Electrical and Electronics Engineers Inc., 2016)
With the emergence of internet and World Wide Web, traditional businesses got a new opportunity to compete globally. Traditional bricks-and-mortar businesses became electronic business (e-business) by utilizing Information and Communication Technology (ICT) tools. A new term of Mobile Commerce (M-Commerce) has created tremendous spectrum of business opportunities for businesses. Although there has been large scale adoption of M-Commerce in developing economies, but little growth is observed in developing economies such as Pakistan. There are doubts that users of M-commerce demonstrate a lack of enthusiasm, which may be due to lack of trustworthiness. Based on the well-known and widely used Technology Acceptance Model (TAM), this research study provides the conceptual framework, underpinning the relationship of trust with the adoption of M-commerce in Pakistan. The aim of this paper is to study the role of trust and its relationship with the acceptance of M-Commerce in Pakistan. © 2015 IEEE.